THE OLDEST ROCKS OF GREECE: FIRST EVIDENCE FOR A PRECAMBRIAN TERRANE WITHIN THE PELAGONIAN ZONE - Anders B.; Reischmann T.; Kostopoulos D.; Poller U. (My University, 2006)
The Pelagonian Zone in Greece represents the westernmost belt of the Hellenide hinterland (Internal Hellenides). Previous geochronological studies of basement rocks from the Pelagonian Zone have systematically yielded Permo-Carboniferous ages. In this study we demonstrate, for the first time, the existence of a Precambrian crustal unit within the crystalline basement of the Pelagonian Zone. The U-Pb single-zircon and SHRIMP ages of these orthogneisses vary from 699 ± 7 Ma to 713 ± 18 Ma, which identify them as the oldest rocks in Greece. These Late Proterozoic rocks, which today occupy an area of c. 20 × 100 km, are significantly different from the neighbouring rocks of the Pelagonian Zone. They are therefore interpreted as delineating a terrane, named here the Florina Terrane. During the Permo-Carboniferous, Florina was incorporated into an active continental margin, where it formed part of the basement for the Pelagonian magmatic arc. The activity of this arc was dated in this study by single-zircon Pb/Pb ages as having taken place at 292 ± 5 Ma and 298 ± 7 Ma. During the Alpine orogeny, Florina, together with the Pelagonian Zone, eventually became a constituent of the Hellenides. Geochemically, the Florina orthogneisses represent granites formed at an active continental margin. Because of the Late Proterozoic ages, this Late Proterozoic active continental margin can be correlated to a Pan-African or Cadomian arc. As the gneisses contain inherited zircons of Late to Middle Proterozoic age, the original location of Florina was probably at the northwestern margin of Gondwana. Similar to other Gondwana-derived terranes, such as East Avalonia, Florina approached the southern margin of Eurasia during Palaeozoic times, where it became part of an active continental margin above the subducting Palaeotethys. These interpretations further indicate that terrane accretion was already playing an important role in the early pre-alpine evolution of the Hellenides.
Keywords: ZIRCON GEOCHRONOLOGY; ND ISOTOPES; NEOPROTEROZOIC BASEMENT; FLORINA TERRANE; PELAGONIAN ZONE; GREECE; Докембрий::Протерозой; Палеозой::Каменноугольная; Палеозой::Кембрийская; Precambrian::Proterozoic; Paleozoic::Carboniferous; Paleozoic::Cambrian